Metode Reverse Circulation Drilling Pada “Approach Bridge” Jembatan Suramadu - Roejanto, Juse; Herol (JURNAL TEKNIK SIPIL, 2024)
The selection of the appropriate drilling method is crucial, especially for offshore projects (conducted on rivers or seas), which generally involve deep drilling lengths and large diameters. One drilling method, aside from the commonly used “Kelly bar system” for land drilling, is the circulation system. For the “Approach Bridge” and “Main Bridge” sections of the Suramadu Bridge, the drilling method employed was the “Circulation” method. The focus of this discussion is on the “Approach Bridge” section, as the drilling depth reaches around 80-90 meters, and the soil conditions are quite varied according to available data. However, in general, clay shale layers were found, a type of soil highly sensitive to disturbances during the drilling process and to weather effects. Therefore, during the drilling process, a slurry stabilizer is required to prevent the collapse of the bore pile walls. The slurry stabilizer used involves mud and bentonite. After the bore pile construction is completed, the piles will be tested to determine their bearing capacity. The bore pile tests are conducted using the Osterberg Cell method, and a Sonic Logging test is also carried out to assess the integrity of the bore piles.